1964
DOI: 10.1083/jcb.23.3.499
|View full text |Cite
|
Sign up to set email alerts
|

AN ELECTRON MICROSCOPE STUDY OF TOBACCO MOSAIC VIRUS LESIONS IN NICOTIANA GLUTINOSA L

Abstract: Ultra-thin sections of Nicotiana glutinosa L. leaves inoculated with a concentrated solution of tobacco mosaic virus were made at short intervals from 0 to 78 hours after inoculation. Eight hours after inoculation, the size of starch grains increased. This was followed by rupture of cytoplasmic and chloroplast membranes. At about 24 hours there was a great increase in number of mitochondria, which persisted until about 60 hours, when some became electron opaque while others appeared to disintegrate. Finally, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0
1

Year Published

1967
1967
2002
2002

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(18 citation statements)
references
References 12 publications
1
16
0
1
Order By: Relevance
“…We have never found, along with the protrusions, any of the ultrastructural alterations of chloroplasts and other cell organelles characteristic of most virus-infections (see, e. g., the exhaustive review by GEROLA 1967). In fact we have never observed any alterations of the membranes or swellings of the thylacoid or fragmentation of grana or breaking of the plastidial envelope: all symptoms which, in addition to the formation of chloroplast protrusions, should be related to osmotic unbalances occurring in cells of virus-infected plants (see, e. g., WEINTRAUB and RAGETLI 1964;GEROLA 1967).…”
Section: Resultsmentioning
confidence: 99%
“…We have never found, along with the protrusions, any of the ultrastructural alterations of chloroplasts and other cell organelles characteristic of most virus-infections (see, e. g., the exhaustive review by GEROLA 1967). In fact we have never observed any alterations of the membranes or swellings of the thylacoid or fragmentation of grana or breaking of the plastidial envelope: all symptoms which, in addition to the formation of chloroplast protrusions, should be related to osmotic unbalances occurring in cells of virus-infected plants (see, e. g., WEINTRAUB and RAGETLI 1964;GEROLA 1967).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to this molecular and physiological evidence for the induction of the HR‐like host response, HR‐associated structural changes in the cells have been observed at the narrow region surrounding leaf tissue from NLLs in several virus–host plant systems showing the HR (Weintraub and Ragetli, 1964; Hayashi and Matsui, 1965; Kolehmainen et al., 1965; Milne, 1966; Israel and Ross, 1967; Da Graca and Martin, 1975; Ehara, 1979). To further characterize the response of Nicotiana species to CMV(Y/GM2)tr, we have investigated the fine structural changes in the cells surrounding the NLLs in N. glutinosa inoculated with CMV(Y/GM2)tr.…”
Section: Introductionmentioning
confidence: 95%
“…There have been earlier reports of the ubiquitous occurrence of TMV in clusions in infected host plants (Esau 1941, Goldstein 1926. Several investigators have reported on the effects of tobacco mosaic virus (TMV) in leaves of Nicotiana tabacum (Weststeijm 1976, Esau and Cronshaw 1967, Edwardson 1966, Weintraub and Ragetli 1964, Favali et al 1974, Betto et al 1972, Gerola et al 1969, Conti et al 1974, Brants 1964, Kontaxis and Schlegel 1962, Wu 1973, Israel and Ross 1967, Shalla 1968, Zaitlin and Boardman 1958, Cech 1967, Milne 1966.…”
mentioning
confidence: 99%
“…TMV synthesis in the chloroplast is still an open question (Esau and Cronshaw 1967). Starch lesions were first observed in chloroplasts by Holmes (1929) and it has been suggested that these lesions develop from starch grains that gradually enlarge (Weintraub and Ragetli 1964).…”
mentioning
confidence: 99%
See 1 more Smart Citation